NMR relaxation parameters from molecular simulations of hydrated inorganic nanopores. Issue 18 (22nd May 2014) - Bhatt, Jayesh S.; McDonald, Peter J.; Faux, David A.; Howlett, Nicholas C.; Churakov, Sergey V.; Brändas, Erkki; Szabados, Ágnes; Surján, Péter
<x xml:space="preserve">Abstract</x> Nuclear magnetic resonance (NMR) relaxometry is a powerful technique to characterize diffusive motion of fluids in nanoporous to microporous media. Molecular simulations can be used to predict NMR relaxation parameters using a dipolar spin–spin correlation function. In this article, molecular dynamics simulations of water diffusion in anomalous 11 Å tobermorite, consisting of three slit pores and one gel pore of width ∼1.0 nm, have been performed. The spin–spin correlation function components corresponding to both 2D and quasi‐2D translation and rotation of water are presented. It was found that motion in the slit pores is highly correlated, leading to a significantly shorter relaxation time compared to bulk water. The correlation between the slit pores and the gel pore was found to be negligible compared to that within either the gel pore or the slit pore exclusively. Nevertheless, this correlation function can be useful in quantifying water diffusion within the slit pores, which occurs primarily through stochastic site jumping. It was found that stronger surface interaction leads to lower relaxation times, while the hydroxyls on the surface help further lower the water relaxation times. © 2014 Wiley Periodicals, Inc.